Síntese e caracterização de compósitos polianilina/poli(estireno-co-divinilbenzeno) para Adsorção de Ânions [SnCl4]²- - Lima, Wolney Arruda de (2013)
In this work were prepared and characterized polyaniline/poly(styrene-co-divinylbenzene) composites by in situ oxidative polymerization of aniline in the pores of styrene-divinylbenzene copolymers. The aim was to obtain composites with high specific surface areas and total pore volumes for use as adsorbents of complex anions [SnCl4]2-. The copolymers with 29 and 84 % of divinylbenzene (DVB) were called PStyDVB 29 and PStyDVB 84, respectively. They were synthesized by suspension polymerization in the presence of inert diluents like toluene and heptane to obtain mesoporous beads with sizes in the range of 400 to 800 μm. Before the oxidative polymerization, the copolymers were swelled with aniline and ethanol mixture at volumetric ratio 20:80. The oxidative polymerization of aniline in the copolymers was carried out using benzoyl peroxide as an oxidant in the presence of hydrochloric or nitric acid as dopant at 25°C in three polymerization cycles. The materials were characterized by infrared spectroscopy with Fourier transform (FTIR), elemental analysis (CNHS), X ray diffraction, thermogravimetry, nitrogen adsorption (specific surface area and pore volume), Scanning Electron Microscopy and Atomic Absorption spectrophotometry. Elemental analysis indicated that the composite doped with HCl adsorb higher amounts of polyaniline (PANI) than using HNO3. The FTIR spectra and X-ray diffraction patterns of the composites were similar to the ones of the copolymers due the low amounts of PANI incorporated. The copolymers had lower thermal stability than composites, and the copolymer PStyDVB 84 had higher thermal stability due to a higher crosslinking degree. The specific surface areas (SBET) and pore volume (Vp) of the composites showed a decrease compared to the respective copolymers, due to the incorporation of polyaniline by homogeneously distributed inside and outside surfaces. The increasing of DVB content in the composites and copolymers favored the formation of high specific surface areas and pore volumes. The adsorption of anion complex [SnCl4]2- by the composites occurred by ion exchange of ions Cl- or NO3-. The results showed that the complex anions [SnCl4]2- adsorption increased with the increasing of hydrochloric acid and tin ion (II) concentrations. The complex anions [SnCl4]2- adsorbed more on the composite PANI/PStyDVB 84 HNO3, although it showed the lowest PANI content, the highest specific surface area and pore volume compared to the other composites. It can be concluded that the anion complex [SnCl4]2- adsorption depends on the number of binding sites and on the porous structure of the composites.